A lightweight approach to mobile multicasting in Wireless Sensor Networks. (7th December 2006) - Ye, Qing; Cheng, Liang
Wireless Sensor Networks (WSN) are envisioned to have significant impacts on many applications. In scenarios such as first responder systems and administrative applications, data sinks are frequently being mobile. In this research, we study one-to-many and many-to-many data communications from stationary sensors to mobile sinks, which is defined as mobile multicasting here. We firstly propose Track and Transmit (TNT), a simple lightweight approach to providing mobile multicasting service in WSN. Its rationale is based on the fact that the mobile sinks will stamp their movement traces in the networks while moving continuously from one location to another. Then we propose Priced TNT (PTNT), which improves the forwarding efficiency of TNT. Compared to Very Lightweight Mobile Multicasting (VLM2), simulations show that both TNT and PTNT are able to dramatically suppress the control overheads, as well as achieve better data delivery-ratio and acceptable delay performances.